PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 16 KUALA PENASO - ', Dahlia; Marhadi, Hendri; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research was carried out starting from the low averages the fourth grade social studies students SDN 16 Kuala Penaso. Of the 23 students who achieved KKM (minimum completeness criteria) only 8 students (34,78%), while 15 students did not complete (65,22%) with an average 53,48. The research problem is Application of Cooperative Learning Model with Type Think Pair Share (TPS) to Improve Learning Outcomes in Grade IV IPS SDN 16 Kuala Penaso? "This study aims to improve learning outcomes IPS fourth grade students of SDN 16 Kuala Penaso through the application of learning models Type Think Pair Share (TPS). This research is a form of Classroom Action Research (CAR), Application of Cooperative Learning Model Type Think Pair Share (TPS) in fourth grade at SDN 16 Kuala Penaso by the number of students 23. The research was conducted in April 2016. Learning to implement cooperative learning model Think Pair Share (TPS). At the first meeting of the first cycle of observation activities for teachers to get a percentage of 78.13%, increasing to 81.25% in the second meeting. At the first meeting of the second cycle revaluation increased by 84.38% and the second meeting of the second cycle assessment of teacher activity reached 90.68%. Assessment of student activity at the first meeting of the first cycle to obtain a percentage of 71.87% and then increased to 78.13% in the second meeting. At the first meeting of the second cycle reached 84.37% and the percentage of the second meeting of the second cycle to obtain a percentage score of 87.50% and increased 53.48 basis of learning outcomes increased to 60.86 in the first cycle and the second cycle increased to 82.61. Based on these results it can be concluded that through the application of cooperative learning model to improve learning outcomes Think Pair Share (TPS) can improve IPS fourth grade students of SDN 16 Kuala Penaso acceptable.Â Key Words : Think Pair Share, learning outcomes IPS